The Social Register: Staying Relevant in the Post-Industrial Age - David Broad (Journal of Public and Professional Sociology)
The Social Register has been since 1888 a defining feature of the American social upper class which has been argued by Baltzell, Domhoff and others as a governing class. From its beginnings in the flowering of the corporate oligarchy in the industrial age, the Social Register has changed relatively little in character or content. Recent journalistic and social scientific examinations of Social Registry have questioned its continuing relevance to the thesis that the social upper class is a governing class. This paper examines some of the foundational work of Domhoff and others and extends that examination to recent developments in the symbolic representations of Social Registry.